Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00787-006-0525-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural problems and autism in children with hydrocephalus

Abstract: Aims: The main objective of this thesis was to explore the cognitive and behavioural consequences of hydrocephalus in children born at term and preterm, with or without myelomeningocele (MMC) and with or without concomitant neurological impairments, such as cerebral palsy (CP), epilepsy or learning disabilities. Material and methods:From a population-based cohort of all 107 children with hydrocephalus born in [1989][1990][1991][1992][1993] 73 of the surviving children were assessed with intelligence tests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 67 publications
4
41
2
Order By: Relevance
“…The elevated ASSQ total score in children with neurological disorders is in accordance with the high rate of ASD symptoms found in studies of children with hydrocephalus [7,9] and epilepsy [11]. Although our sample represented a heterogeneous group including a range of neurological disorders, the combined parent and teacher ASSQ of 14.1% scoring above the 98 th percentile is in agreement with studies indicating that certain diagnoses included in our sample, for instance cerebral palsy [15], entail a heightened risk of ASD.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The elevated ASSQ total score in children with neurological disorders is in accordance with the high rate of ASD symptoms found in studies of children with hydrocephalus [7,9] and epilepsy [11]. Although our sample represented a heterogeneous group including a range of neurological disorders, the combined parent and teacher ASSQ of 14.1% scoring above the 98 th percentile is in agreement with studies indicating that certain diagnoses included in our sample, for instance cerebral palsy [15], entail a heightened risk of ASD.…”
Section: Discussionsupporting
confidence: 79%
“…Note that children may have more than one diagnosis, and that children with disorders co-existing with neurological disorders were classified as belonging to the neurological disorder group. It is also important to be aware that the presence of intellectual disability in children with neurological disorders is associated with increased risk of ASD [5,7,9,14,15,45]. We therefore controlled for the presence of intellectual disability (as reported by parents) in the present analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy, learning disability, language delay and tetraplegic, hemiplegic, and mixed types of CP were found to be associated factors for the coexistence of autistic disorder in our study. Several investigators have described a connection between autism and the severity of brain dysfunction 6,9 . In our study, autism was found to be more common in children with signs of a more extensive brain lesion, resulting in epilepsy, learning disability, or tetraplegic or mixed types of CP.…”
Section: Discussionsupporting
confidence: 51%
“…The second group includes studies of whether CP is associated with autism in various medical disorders. CP was found to be linked to autism in children with hydrocephalus, 9 retinopathy of prematurity, 10 and visual impairment 11 . Nordin and Gillberg 12 examined 177 children with heterogeneous clinical diagnoses causing learning or motor disability, or both, and found that four (10.5%) of the 38 children with CP had autistic spectrum disorders (ASD).…”
mentioning
confidence: 99%